5-Substituted Pyrimidine and 7-Substituted 7-Deazapurine dNTPs as Substrates for DNA Polymerases in Competitive Primer Extension in the Presence of Natural dNTPs - Cahová, Hana; Panattoni, Alessandro; Kielkowski, Pavel; Fanfrlík, Jindřich; Hocek, Michal (ACS chemical biology, 2016)
A complete series of 5-substituted uracil or cytosine, as well as 7-substituted 7-deazaadenine and 7-deazaguanine 2'-deoxyribonucleoside triphosphates (dNTPs) bearing substituents of increasing bulkiness (H, Me, vinyl, ethynyl, and phenyl) were systematically studied in competitive primer extension in the presence of their natural counterparts (nonmodified dNTPs), and their kinetic data were determined. The results show that modified dNTPs bearing π-electron-containing substituents (vinyl, ethynyl, Ph) are typically excellent substrates for DNA polymerases comparable to or better than natural dNTPs. The kinetic studies revealed that these modified dNTPs have higher affinity to the active site of the enzyme-primer-template complex, and the calculations (semiempirical quantum mechanical scoring function) suggest that it is due to the cation-π interaction of the modified dNTP with Arg629 in the active site of Bst DNA polymerase.
Keywords: Substrate Specificity; puriny; kinetika; DNA-dependentní DNA-polymerasy; nukleotidy; Kinetics; Purines; substrátová specifita; Pyrimidines; Nucleotides; Quantum Theory; DNA-Directed DNA Polymerase; pyrimidiny; kvantová teorie